Glutamatergic agents for schizophrenia: current evidence and perspectives - Zink, Mathias; Correll, Christoph U. (Expert review of clinical pharmacology, 2015)
Suboptimal outcomes in schizophrenia are a consequence of lacking insight into the etiology, biomarkers and treatment-relevant subgroups, the therapeutic restriction to dopaminergic-modulating antipsychotics that fail to significantly improve negative and cognitive symptoms, non-adherence, and, in the case of treatment-resistance, the underutilization of clozapine. Evidence suggests additional, extra-dopaminergic abnormalities in amino acid neurotransmission, particularly the glutamatergic system. Antidopaminergic antipsychotics modulate this system on several levels, as do mood stabilizers, including lamotrigine, topiramate and pregabaline. Recently, agonists at metabotropic glutamate receptors and glycine uptake inhibitors failed in large placebo-controlled trials for schizophrenia. Problems to overcome for successfully leveraging glutamatergic agents for schizophrenia are patient selection, focus on positive symptoms and late disease stages, and dose-response relationships. Because glutamate guides processes of brain development and maturation, clinical research should focus on the at-risk mental state or first-episode psychosis, address cognition and negative symptoms and use monotherapy designs in parallel to augmentation strategies.